Analysis of the Internal Control System for Merchandise Inventory at Alfamart Merapi, Tebeng Gardens, Bengkulu - Lausa Saresa; Sulisti Afriani; Yun Fitriano (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the internal control system for merchandise inventory at Alfamart Merapi Kebun Tebeng Bengkulu. The results showed that the internal control system for merchandise inventory at Alfamart Merapi Kebun Tebeng Bengkulu was compatible with Mulyadi's theory (2018: 488). In the organizational element, there is a schedule and committee involved in the stock opname. The authorization system and recording procedures are appropriate, where the monthly Stock Opname report is signed by the shop head and the daily Stock Opname is signed by the employee of the shift holder, the recording is based on the results of the monthly and daily (partial) Stock Opname reports calculated based on an invoice containing the type of goods, price of goods and quantity of goods. Healthy practice, there is conformity in the application of the internal control system for merchandise inventory, where invoices have been printed serial numbers and issued by DEPO Alfamart, Stock opname is carried out twice (monthly and daily) using the PDA system. In this element of healthy practice control there is an inconsistency with Mulyadi's theory (2018: 44), where the quantity and other inventory data listed in the 3rd and 2nd part of the physical count card are matched by the physical count card holder before the data is collected. listed in part 2 of the physical count card is recorded in the list of physical count results, because at Alfamart Kebun Tebeng, the quantity and inventory data are matched based on the invoice sent by DEPO